2018
DOI: 10.7717/peerj.5732
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sports expertise level on attention in multiple object tracking

Abstract: BackgroundThis study aimed to investigate whether performance in a multiple object tracking (MOT) task could be improved incrementally with sports expertise, and whether differences between experienced and less experienced athletes, or non-athletes, were modulated by load.MethodsWe asked 22 elite and 20 intermediate basketball players, and 23 non-athletes, to perform an MOT task under three attentional load conditions (two, three, and four targets). Accuracies were analyzed to examine whether different levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
66
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(75 citation statements)
references
References 43 publications
7
66
1
1
Order By: Relevance
“…We found no difference in the tracking performance between skilled basketball players and nonathletic college students on the MOT task. These results are inconsistent with those observed in another study using a MOT task that found that team ball players have better visual attention than non-athletes (Qiu et al, 2018). These discrepant results are likely attributable to the target speed being too slow to assess this skill for both skilled basketball players and nonathletic college students.…”
Section: Visual Tracking Performance For the Number Of Targetscontrasting
confidence: 88%
See 1 more Smart Citation
“…We found no difference in the tracking performance between skilled basketball players and nonathletic college students on the MOT task. These results are inconsistent with those observed in another study using a MOT task that found that team ball players have better visual attention than non-athletes (Qiu et al, 2018). These discrepant results are likely attributable to the target speed being too slow to assess this skill for both skilled basketball players and nonathletic college students.…”
Section: Visual Tracking Performance For the Number Of Targetscontrasting
confidence: 88%
“…When the ability of NBA players at different positions in the game to track multiple targets was investigated, the result showed that the target tracking speed of guards was significantly better than that of forwards and the center and that target tracking speed ability can predict and evaluate the performance of a match (Mangine et al, 2014). Many literature indicated that sport training improves visual attention performance, (Qiu et al, 2018;Heppe et al, 2016;Verburgh et al, 2014). In most sports, athletes must complete the established technical actions as rapidly as possible (capture effective information in a short period of time) and as accurately as possible (showing a strong spatial positioning ability).…”
Section: Visual Tracking Performance Associated With Target Speedmentioning
confidence: 99%
“…Collectively, these systems can be overloaded when individuals attempt to multitask and divide their attentional capacity between selecting information and deciding on action strategies. Consequently, it is unsurprising that in sports, attention appears to be related to sport practice (Kioumourtzoglou et al, 1998;Williams and Davids, 1998;Heppe et al, 2016;Sanchez-Lopez et al, 2016;Qiu et al, 2018;Meng et al, 2019). This has been shown to be the case in sports such as martial arts (Sanchez-Lopez et al, 2016), basketball (Qiu et al, 2018), soccer (Heppe et al, 2016), and volleyball (Kioumourtzoglou et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it is unsurprising that in sports, attention appears to be related to sport practice (Kioumourtzoglou et al, 1998;Williams and Davids, 1998;Heppe et al, 2016;Sanchez-Lopez et al, 2016;Qiu et al, 2018;Meng et al, 2019). This has been shown to be the case in sports such as martial arts (Sanchez-Lopez et al, 2016), basketball (Qiu et al, 2018), soccer (Heppe et al, 2016), and volleyball (Kioumourtzoglou et al, 1998). However, the differences in attention responses seem to depend on the influence of a variety of information processing demands associated with each sport's modality (Singer, 2000;Voss et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Entre las variables psicológicas más relacionadas con el rendimiento deportivo en prácticamente todos los deportes estudiados se encuentran la autoconfianza (González, Valdivia, Cachón, Zurita y Romero, 2017;Selmi, Rebai, Chtara, Naceur y Sahli, 2018), el control de estrés (Godoy-Izquierdo, Vélez y Godoy, 2007;Junichi y Hajime, 2007), la motivación (Irwin y Feltz, 2016; Rodrigues, Da Costa, Samulski y Noce, 2007;Zeelenberg, Nelissen y Pieters, 2008) y la atención (Mora, Zarco y Blanca, 2001;Qiu et al 2018), entre otras.…”
unclassified